Population Features of Visually Impaired Children and Their Parents Living in Hungary (European Journal of Mental Health, 2021)
This exploratory research (2014–2019) was conducted among visually impaired children aged 0–14 years and their parents. The paper focuses on the crucial features of the healthcare and pedagogical services provided for visually impaired children and analyses the situation of parents raising them. In order to explore the population characteristics of visually impaired children in Hungary, we relied on two major data sources: the census data of the Hungarian Central Statistical Office between 1990–2016, and the examination documents of the Corps of Pedagogical Services of Visually Impaired Children between 2009–2013. The research included data of 1,432 visually impaired children. In order to survey the situation of these children’s parents, we conducted semi-structured, individual interviews. We investigated the retrospective narratives of 39 mothers and 29 fathers through narrative categorical content analysis and performed the situation analysis of the parents, using the model of game theory between humans and environment, whilst we also took into consideration the Hungarian and international methodological context for researching parents raising visually impaired children. Results suggest that the population of visually impaired children is under transformation: visually impaired groups based on the classical interpretation of visual performance are being replaced by new groups governed by needs. What the parents of such children seem to lack the most in the Hungarian care system are the opportunities for physical and mental relief. It would be vital to improve the situation of the parents concerned by more flexible special education and social services that could support both single parents and couples to overcome their difficulties.